2021
DOI: 10.3389/fnut.2021.652311
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake of Vegetables and Cooking Oil Was Associated With Drug-Induced Liver Injury During Tuberculosis Treatment: A Preliminary Cohort Study

Abstract: Background and Purpose: Drug-induced liver injury is challenging during tuberculosis treatment. There is no epidemiological data investigating the relation between dietary intake and the risk of drug-induced liver injury during tuberculosis treatment. The aim of this study is to investigate the association of food and nutrient intake with the incidence of tuberculosis-drug-induced liver injury.Methods: A cohort study was conducted in two city-level tuberculosis-specialized hospitals in Linyi City and Qingdao C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 39 publications
2
4
0
Order By: Relevance
“…The decreased levels of ALT, AST, and MDA in the present study agree with previous findings that represented the protective effect of VC on the liver of carbon tetrachloride-intoxicated rats ( 28 , 29 ). Several studies have reported that VC produces a protective effect against drugs and chemical agents that induce hepatotoxicity ( 28 , 29 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The decreased levels of ALT, AST, and MDA in the present study agree with previous findings that represented the protective effect of VC on the liver of carbon tetrachloride-intoxicated rats ( 28 , 29 ). Several studies have reported that VC produces a protective effect against drugs and chemical agents that induce hepatotoxicity ( 28 , 29 ).…”
Section: Discussionsupporting
confidence: 93%
“…The decreased levels of ALT, AST, and MDA in the present study agree with previous findings that represented the protective effect of VC on the liver of carbon tetrachloride-intoxicated rats ( 28 , 29 ). Several studies have reported that VC produces a protective effect against drugs and chemical agents that induce hepatotoxicity ( 28 , 29 ). The target of VC is the mitochondria, preventing mitochondrial swelling, mitochondrial membrane potential dissipation, and ROS burst, thereby preventing hepatic apoptosis; these effects may oppose the action of MTX ( 15 , 20 ).…”
Section: Discussionsupporting
confidence: 93%
“…In addition to drug treatment, the potential role of dietary components hasreceived increased attention. Previous studies have shown the effectiveness of healthy dietary patterns and components for the prevention of CVD and other diseases [ 2 , 3 , 4 ]. Fish is rich in various nutrients (e.g., protein, vitamin D and polyunsaturated fatty acids) and may have a beneficial role in preventing CVD events [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between protein, micronutrients deficiency and the incidence of TBLI was rarely explored and may be a future research direction. Our recent cohort study ( 108 ) indicated that a high vegetable intake and a low cooking oil intake were associated with a reduced risk of TBLI. An optimal dietary pattern may be further investigated for reducing the risk of TBLI.…”
Section: Discussionmentioning
confidence: 98%